2011
DOI: 10.1007/s00704-011-0554-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual temperature and precipitation variations over the Litani Basin in response to atmospheric circulation patterns

Abstract: This study examines the sensitivity of a mid-size basin's temperature and precipitation response to different global and regional climate circulation patterns. The implication of the North Atlantic Oscillation (NAO), El Niño Southern Oscillation (ENSO), Indian Monsoon and ten other teleconnection patterns of the Northern Hemisphere are investigated. A methodology to generate a basin-scale, longterm monthly surface temperature and precipitation time series has been established using different statistical tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…This result expresses the nature of the EA/WR pattern during autumn when south‐eastern winds mainly transport warmer airflow from central Russia to Finland. Ramadan et al () showed negative relationships between SAT and the EA/WR pattern over western Lebanon (north‐eastern Africa in eastern Mediterranean; see also Krichak et al , ) during 1900–2008. Similarly, Lim and Kim () reported negative correlations between the EA/WR pattern and winter (December to February) SAT variations over the Arctic region during 1979–2011.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result expresses the nature of the EA/WR pattern during autumn when south‐eastern winds mainly transport warmer airflow from central Russia to Finland. Ramadan et al () showed negative relationships between SAT and the EA/WR pattern over western Lebanon (north‐eastern Africa in eastern Mediterranean; see also Krichak et al , ) during 1900–2008. Similarly, Lim and Kim () reported negative correlations between the EA/WR pattern and winter (December to February) SAT variations over the Arctic region during 1979–2011.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, a negative correlation between SAT and the SCA pattern over the south and west of Europe has been reported;, e.g. El Kenawy et al () concluded that the above‐average SAT over Spain during 1920–2006 was negatively correlated with the SCA pattern; Ramadan et al () showed a similar correlation for summer season in western Lebanon and Toreti et al () a weak negative correlation between summer SAT in Italy and the SCA pattern.…”
Section: Discussionmentioning
confidence: 97%
“…Törnros (2013) indicated that during negative (positive) MOI phases the probability of above average winter precipitation is 22% (59%), respectively. The North-Sea Caspian-Sea Pattern (NCP) and the East Atlantic -Western Russia (EA-WR) were also found significantly correlated with annual rainfall in the Levant and Israel (Kutiel and Paz, 1998;Krichak et al, 2002;Kutiel and Benaroch, 2002;Yosef et al, 2009;Krichak et al, 2014) and in the Litany Basin, located in southern Lebanon, as exemplified by Ramadan et al (2012). In addition, Ramadan et al (2012) found that the rainfall in the Litany Basin is influenced by the Tropical/Northern Hemisphere Pattern, the East Atlantic Pattern and the Polar/Eurasia Pattern.…”
Section: Introductionmentioning
confidence: 91%
“…Most drought studies deal with annual or monthly time-scales (e.g. Dunkeloh and Jacobeit, 2003;Inbar and Bruins, 2004;Xoplaki et al, 2004;Ziv et al, 2006;Ramadan et al, 2012). However, even dry periods on a shorter time-scale than the monthly or the seasonal may have severe environmental and hydrological implications.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the Mediterranean Oscillation is linked to the NAO especially in winter (Dünkeloh and Jacobeit, ) it is therefore also logical to examine the region's precipitation regime in terms of the Mediterranean Oscillation Index (MOI) which is expressed as differences in sea level pressure (SLP) or geopotential heights between the WM and EM. Although winter precipitation in the WM (Gonzalez‐Hidalgo et al ., ) and EM (Ramadan et al ., ) has been shown to have a negative and positive correlation with the MOI, respectively, this relationship has not been addressed in detail.…”
Section: Introductionmentioning
confidence: 99%